Diastereodivergent Synthesis of the Quinolizidine‐Indolizidine Alkaloids of the Leontidine/Camoensine Family. Issue 17 (5th May 2021) - Wagner, Stefan; Sigl, Susanne; Schenkl, Melanie; Breuning, Matthias
Abstract: Leontidine and camoensine, the main representatives of the small quinolizidine‐indolizidine alkaloid subgroup, are characterized by an inner bispidine system to which a 2‐pyridone and a pyrrolidine are fused on opposite sides. We efficiently synthesized both natural products from the commercially available and abundant alkaloid cytisine, which was converted into the key intermediate, N‐ Boc‐11‐oxocytisine, by iodine oxidation and protection. Grignard addition, Paal‐Knorr type cyclization, and hydrogenation delivered endo‐ pyrrolidine fused leontidine, while the reversed reaction order, viz . reduction, Sakurai allylation, and ring closure, afforded exo‐ pyrrolidine annulated camoensine. Hydrogenation and deoxygenation of the pyridone moieties provided four further alkaloids, tetrahydroleontidine, camoensidine, 11‐epileontidane and leontidane. In addition, the artificial alkaloid isoleontidine, carrying an endo‐ fused pyrrolidine on the same side as the pyridone, was prepared from C‐13 oxidized cytisine. Abstract : The tetracyclic alkaloids of the leontidine/camoensine family, which all possess the rare natural quinolizidine‐indolizidine skeleton, were prepared from the commercially available and abundant alkaloid cytisine. The key intermediate was N‐ Boc‐11‐oxocytisine, which can be converted in just a few steps into the natural products with an endo‐ or, optionally, exo‐ α, N ‐fused pyrrolidine.